Interplay between dynamics of polymeric templates and adaptive synthesis of species from dynamic combinatoriall libraries - Qi, Dawei (fi=Turun yliopisto|en=University of Turku|, 2025)
Dynamic combinatorial chemistry (DCC) utilize reversible covalent reactions to synthesize dynamic combinatorial libraries (DCLs) of interconvertible products. The output of DCL could be directed by the template effect, in a way that the products restructure for self-assembling with the template at the free energy minimum. Typically, the templates are discrete small molecules with relatively elementary chemical structure and static conformation. In this thesis, the dynamics of polymeric template was studied for controlling the self-assembly in DCLs. In general, a polymeric template will complex with the DCL of macrocyclic disulfides (DCMs) synthesized from an anionic dithiol building block, then response with different dynamics interactive with the structural transition of DCMs. As a result, this study brought two new fundamental factors to the template effect, one is the conformational dynamics, another is the entropy-driven configurational dynamics. In the first project, the conformational dynamics was studied during the folding process of the polymer-DCMs complexation. The DCMs adjusted their structures in real time to adapt with and control the conformational changes during the folding process. The DCMs could further re-adapt to adjust the folding for building high drug-loading content drug delivery systems (DDSs) against drug-resistant cancer. The second project explored the entropy-driven configurational dynamics in the polymer-DCM complexation. The increased binding of DCMs decreased the conformational entropy. To compensate for the entropy loss, the DCMs restructured for faster binding kinetics and high configurational entropy. While the increased addition of a kosmotropic salt NaCl applied penalty to the solvation entropy, which enhanced hydrophobic aggregation and production of DCMs in larger size. In the third project, the polymeric templates from the first two projects were combined as a diblock copolymeric template, from which the interplay between two different dynamics was studied. The increased binding of DCMs to the copolymeric template gradually initiated the two dynamics sequentially due to the difference in DCMs’ binding affinity to each chain block.